HYPNOPARENTING TERHADAP TEMPER TANTRUM PADA ANAK PRASEKOLAH DI TK ISLAM TERPADU BINA INSANI KECAMATAN MOJOROTO KOTA KEDIR - Anugraheni, Ifana (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2017)
Hypnoparenting can improve the quality of parent and child communication. Hypnoparenting isdone by saying a sentence that directs positive behavior to the child, so that it can control thebehavior of tantrums. The results of the initial survey of the 22 preschool children in TK IslamTerpadu Bina Insani Kecamatan Mojoroto Kota Kediri, obtained 19 children (86%) had tempertantrums. This shows that children who have temper tentrum still high. The purpose of this studywas to determine the effect hypnoparenting to temper tantrums in preschoolers in TK IslamTerpadu Bina Insani Kecamatan Mojoroto Kota Kediri. The research design was quasiexperimental study (Time Series Design). The population studied were all children of preschoolaged in TK Islam Terpadu Bina Insani Kecamatan Mojoroto Kota Kediri totaling 19 children,with total sampling technique. Results of the study were analyzed using the Wilcoxon statisticaltest. Results Wilcoxon test, it was found that p-value = 0.020, smaller than ɑ = 0,05, so H0rejected and H1 accepted,meaning that there is influence hypnoparenting to temper tantrums inpreschool aged in TK Islam Terpadu Bina Insani Kecamatan Mojoroto Kota Kediri. Based on theresults of the study are expected parents can continue hypnoparenting every day so that childrencan be independent and ready for the future well.